The Role of PKK in the Immunization Progmmme - Soegen Soegijanto; Dwi Atmadji S.; Parwati Setiono B.; Ismoedijanto Ismoedijanto; Widodo D. M.; Aried Kaspan (Indonesian Pediatric Society, 1989)
A mid term evaluation of the immunization programme had been carried out in East Java from November 27, 1987 to December 6, 1987. The team consisted of various multidisciplines comprising members of the WHO (3), the Department of Health (4), the Medical Faculty (1), the PKK group (1), and Bangdes. Data showed that the Posyandu, the Health Centres, Hospitals and private doctors contributed to the programme by 69%, 28%, 2% and 1% respectively. It was obvious that although not satisfactory, the Posyandu was by for the mostly committed, reflecting the role of the PKK group especially in terms of encouraging mothers to bring their children to the Posyandu. As one face facts of low educated mothers, mothers being trapped in their routine daily activities, or having had inconvenient medical experience, a low motivation towards immunization might be anticipated, which in turn leads to a low coverage of immunization. Taking into consideration of how the PKK group plays its role in the immunization programme, attempts made to improve knowledge on immunizable diseases and their measures for prevention would undoubtly be an important means of support to gain the aim of immunization.